Optimal Fiscal Policy and Government Provision of Contingent Liabilities : The Example of Government Loan and Deposit Guarantees. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
The optimal provision of loan guarantees or deposit insurance is examined in the context of an overlapping generations model. It is demonstrated that even in the face of a market imperfection that precludes diversification of the private sector's loan portfolio to eliminate risk, full government guarantee of private sector loans (or deposits) is suboptimal. The results of the paper suggest that although some degree of guarantee is appropriate, the design of such policies should be tempered to avoid an inefficient level of capital accumulation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet